Manajemen Pendidikan Karakter Leaderpreneur bagi Peserta Didik pada SMA Al-Aziz Islamic Boarding School di Kabupaten Bandung Barat - Aulia Rohmah; Asep Dudi Suhardini; Muhardi (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
His study aims to describe the management of leaderpreneur character education for students at Al-Aziz Islamic Boarding School in West Bandung Regency. This study uses a qualitative approach with a case study method. The research subjects include the principal and teachers. Data collection techniques are carried out through interviews, observations, and documentation studies. Research informants include the principal and teachers. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions with data validity tests using source and technique triangulation. (1) planning for leaderpreneur character education is carried out systematically through the integration of the school's vision and mission, curriculum, and flagship programs based on Islamic values; (2) organizing character education is carried out through a clear division of roles and responsibilities between the principal, teachers, dormitory supervisors, and student organizations; (3) implementation of leaderpreneur character education is realized through project-based learning, habituation of dormitory life.